A reckoning with the maintenance of the built environment, a Sisyphean task - Maria Luisa Germanà (Vitruvio: International Journal of Architectural Technology and Sustainability)
Maintenance concerns most of the artifacts, referring simultaneously to the socio-cultural, technical and managerial spheres. Contemporary scenarios impose an overall rethinking, where key-topics such as tradition, consumerism, sustainability and digitization become pivotal in the search for suitable production models, between post-industrial and neo-craftsmanship, in order to have fresher references for the maintenance activities.